CLINICAL CHARACTERISTICS AND OUTCOMES OF ACUTE CORONARY SYNDROMES IN A GROUP OF IRAQI PATIENTS (Iraqi Journal of Medical Sciences, 2017)
Background:Coronary artery disease (CAD) is one of the most common diseases in the world. Acute coronary syndromes (ACS) represent the acute life-threatening phase of CAD. Epidemiology and management of ACS patients differ a lot between countries and there is a wide gap between guidelines and clinical practice. Objective:To assess contemporary data on clinical characteristics and outcomes of patients with ACS in the Medical City Complex and to evaluate adherence to the guidelines’ recommended treatment.Methods: This is a descriptive study registry, started on January 2014 to June 2014, and involved 348 patients with ACS in the Medical City Complex.Results: The mean age of this study's population was (60.3±11.2 years), ranging between 29 to 90 years old. Most of patients were males (61%). Only 233 (67%) patients have typical angina. Symptom onset-to-admission time was delayed (? 12 hours) in 65% of patients. The final diagnosis was: ST elevation myocardial infarction (STEMI) in 126 (36.2%), non ST elevation myocardial infarction (NSTEMI) in 40 (11.4%), and unstable angina (UA) in 182 (52.3%) of patients. Electrocardiography was normal in 29% of patients with UA and 10% of patients with NSTEMI. Anterior territory was the most common location of ischemia (77%). Hypertension (47.9%) was the most significant risk factor followed by diabetes mellitus (41.6%) and smoking (31.8%). Reperfusion therapy for patients with STEMI was applied in 73(57%) patients: 56 (44.4%) by thrombolytic therapy, 24 (19%) by percutaneous coronary intervention (PCI) and 3 (2.3%) by emergency CABG. Overall in-hospital mortality was 7.7% (15%, 7.5% and 2.7% for STEMI, NSTEMI, and UA respectively).Conclusion: There is lack of awareness of ischemic symptoms among our patients. There is high incidence of risk factors that can be modified by primary and secondary measures. There is underutilization of invasive management. We have a high mortality rates in patients with ACS.Keywords: Acute coronary syndromes, registry, in-hospital outcome DOI: 10.22578/IJMS.14.4.3
Keywords: Acute coronary syndromes; registry; inhospital outcome